2017
DOI: 10.1007/s12094-017-1806-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aspirin on circulating tumor cells in metastatic colorectal and breast cancer patients: a phase II trial study

Abstract: Aspirin could decrease CTCs numbers and block EMT transition in MCC patients and part of MBC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…However, we did not find a significant association between menopause status, tumor site, hormone receptor, HER2 expression status, and CTCs ( P > .05). In addition, compared with our previous data, 75% of MBC patients had CTC numbers greater than 5/7.5 mL of PB . Here, we found that 31.1% (9/29) of patients had CTC numbers greater than 5/7.5 mL of blood.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…However, we did not find a significant association between menopause status, tumor site, hormone receptor, HER2 expression status, and CTCs ( P > .05). In addition, compared with our previous data, 75% of MBC patients had CTC numbers greater than 5/7.5 mL of PB . Here, we found that 31.1% (9/29) of patients had CTC numbers greater than 5/7.5 mL of blood.…”
Section: Resultssupporting
confidence: 50%
“…In addition, compared with our previous data, 75% of MBC patients had CTC numbers greater than 5/7.5 mL of PB. 21 Here, we found that 31.1% (9/29) of patients had CTC numbers greater than 5/7.5 mL of blood.…”
Section: Patient Characteristics and Ctc Evaluation At Baselinementioning
confidence: 49%
See 2 more Smart Citations
“…Though the impact of platelet inhibition on CTC did not correlate with the platelet inhibition, aspirin therapy was favorable in reducing the release of platelet-angiogenic proteins ( 94 , 115 ). Another phase II trial with metastatic cancer patients reported that aspirin treatment significantly reduced CTC numbers in metastatic CRC but did not have significance in metastatic breast cancer ( 116 ).…”
Section: Platelet Metabolism Targeted Non-steroidal Anti-inflammatorymentioning
confidence: 99%